System-level co-simulation for embedded systems - Mossaad Ben Ayed; Ayman Massaoudi; Shaya A. Alshaya; Mohamed Abid (AIP Advances, 2020)
The technological revolution affects the growth of systems in terms of functionality and complexity. Industries of embedded systems become increasingly an area of interest for researchers to develop Computer-Aided Design (CAD) environments to support at the same time the complexity in terms of different components and functionalities in terms of application programming interface and libraries. Mainly, CAD tools based on multi-level co-simulation are challenged by the time-to-market constraint. As known, the behavior description at a higher level provides a speedy simulation, but it suffers from bad accuracy. Therefore, describing a customized model for a system behavior with sufficient functional details at an earlier stage of modeling is a great challenge to researchers. As an attempt to overcome the last challenge, this paper presents a co-simulation model based on a synchronization methodology to ensure the verification between the conceptual level and the functional level. The proposed system-level co-simulation model is implemented to interfaces to provide the switch context in the case of the Arena and the Simulink/Matlab environments. The evaluation was performed by using two case studies with different domains to prove the effectiveness of the proposed system-level co-simulation interfaces.